AB0684 Proposed criteria for activity, damage and impact of juvenile idiopathic arthritis associated uveitis: consensus effort from the multinational interdisciplinary working group for uveitis in childhood (miwguc). (23rd January 2014) - Foeldvari, I.; Heiligenhaus, A.; Edelstein, C.; Anton, J.; Saurenmann, T.; Bodaghi, B.; Kotaniem, K.; Nielsen, S.; Sandfeld, L.; Brumm, G.; Rabinovitch, E.; Ramanan, A.
Abstract : Background: Uveitis is the most common extraartricular manifesation of juvenile idiopathic arthritis (JIA). Uveitis, a potentially blinding disorder, is present in approx 10-18% of JIA patients, with a wide spectrum of presentations. Despite advances in treatment of childhood arthritis there are no definitions for assessment of activity, damage and impact of JIA associated uveitis. Objectives: The purpose of our efforts was to develop and gain consensus on such definitions Methods: At the second consensus meeting of the MIWGUC group, using a Delphi method we developed definitions for activity, damage and impact of disease based on already published outcome measures [1 ]. Results: Conclusions: We will validate these proposed definitions propsectively in a JIA associated uveitis cohort. Based on the results, we will weight these measures to develop an overall scoring system. References: Heiligenhaus, A., et al., Proposed outcome measures for prospective clinical trials in juvenile idiopathic arthritis-associated uveitis: A consensus effort from the multinational interdisciplinary working group for uveitis in childhood (MIWGUC). Arthritis Care Res (Hoboken), 2012. Disclosure of Interest: None Declared